Synthesis and evaluation of a pyrazinoic acid prodrug in Mycobacterium tuberculosis - Fernandes, Joao Paulo-dos Santos; Pavan, Fernando Rogério [UNESP]; Leite, Clarice Queico Fujimura [UNESP]; Andres Felli, Veni Maria (Elsevier B.V., 2014)
Tuberculosis (TB) is a disease caused mainly by infection of Mycobacterium tuberculosis affecting more than ten million people around the world. Despite TB can be treated, the rise of MDR-TB and XDR-TB cases put the disease in a worrying status. As pyrazinamide-resistant strains exhibit low or none pyrazinamidase activity, it is proposed that the active form of pyrazinamide (PZA) is pyrazinoic acid (POA), although this acid has poor penetration in mycobacteria. In this work, we present a convenient one-pot synthesis of 2-chloroethyl pyrazinoate, and its activity in M. tuberculosis H(37)Rv (ATCC27294) in MIC assay using the MABA technique. The obtained MIC of the compound was 3.96 g/mL, and discussion about the activity profile of some previously evaluated pyrazinoates is also performed. (C) 2013 King Saud University. Production and hosting by Elsevier B.V. All rights reserved.
Keywords: Antimycobacterial agent; Ester synthesis; Prodrug; Pyrazinoic acid; Tuberculostatic